Correction: Cs2NaGaBr6: a new lead-free and direct band gap halide double perovskite. Issue 34 (27th May 2020) - Saeed, Yasir; Amin, Bin; Khalil, Haleema; Rehman, Fida; Ali, Hazrat; Khan, M. Imtiaz; Mahmood, Asif; Shafiq, M.
Abstract : Correction for 'Cs2 NaGaBr6 : a new lead-free and direct band gap halide double perovskite' by Yasir Saeed et al., RSC Adv., 2020, 10, 17444–17451, DOI: ; 10.1039/D0RA01764G .